Arab Countries in Transition : Economic Outlook and Key Challenges. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
In spite of deepening and spreading conflicts in the region, as well as, in many cases, a challenging internal socio-political environment, the Arab Countries in Transition (Egypt, Jordan, Libya, Morocco, Tunisia and Yemen) have broadly maintained macroeconomic stability. At the same time, however, their economies are not delivering the growth rates needed for a meaningful reduction in unemployment, in particular for the youth and women. Notwithstanding diversity of conditions, countries should quickly advance structural reforms to foster higher and more inclusive growth, and continue to strengthen fiscal and external buffers to maintain stability amid heightened uncertainty. Coordinated support from the international community will be crucial in the form of financing, improved trade access, and capacity building assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet